POTENSI BISNIS WEDDING ORGANIZER DI KOTA MEDAN SEBAGAI SALAH SATU MULTIPLIER EFFECT INDUSTRI MICE DI KOTA MEDAN - JUNI ANGGRAINI (LP2MTBM MAKARIOZ, 2020)
This study aims to analyze the business potential of wedding organizers in the city of Medan. The city of Medan as one ofthe MICE destinations in Indonesia that the Government has put in place must develop the potential of the MICE industry inthe city. The wedding organizer business has the potential to increase state revenue, develop the economy of the NorthSumatra area, and reduce unemployment in Medan. This research explores the bride and groom in the city of Medan inpreparing their wedding plans. The population used is the wedding organizer and the bride and groom who use the weddingorganizer services in carrying out their wedding. Data collection techniques are done by interview and library study. Theresults of this study are based on the perception of wedding organizers as business people as well as consumers who usethe services of the wedding organizer, found that Medan City based on the needs of the residents of the city requireswedding organizer services in carrying out a perfect wedding without any flaws that can leave a good impression on theinvited guests.